Design of Reporting, Evaluation, and Monitoring Application for Student Organization in University - Rayinda Pramuditya Soesanto; Afrin Fauzya Rizana; Luciana Andrawina (International Journal of Innovation in Enterprise System, 2019)
In few decades, the development of information system has been increased rapidly. It is because most organization in various sector of industries, commerce, government, or even education become highly dependent on the use of information system. The purpose of this study is to design the application that will facilitate the reporting, evaluation, and monitoring activities of student organization based on what user needs. The object of this study is student affair department in one of faculty in one of universities in Indonesia. The method employed in this study to design the system is waterfall. The system designed in this study is focus on the activities related to student organization activities. The result of this study found that there are eight dimensions of web quality that has to be fulfilled by the system according to the result of focus group discussion and Delphi method. The system designed in this study was adjusted to the needs that have been defined previously. Keywords—Information system design, student organization, waterfall method